Otaku vampire's love bite. 2 - Suzuki, Julietta (Shojo beat manga., 2025)
"Hina's new best friends Kyuta and Hoshino are in dire straits when their club's costumes get ruined days before the college festival! All is not lost though, and Hina is very excited to lend a hand (and Viktor's entire wardrobe) at this classic Japanese event. But her otaku joy at cosplaying in a maid cafe is tarnished when a strange customer challenges everything she thought she knew about her own kind!"--Back cover.